Influencing Factors and Differences in Born Aggregometry in Specialized Hemostaseological Centers: Results of a Multicenter Laboratory Comparison - Kaiser, Thorsten; Liebscher, Karin; Scholz, Ute; Pfrepper, Christian; Netto, Jeffrey; Drogies, Tim; Tiebel, Oliver; Knöfler, Ralf; Krause, Michael (TH Open, 2022)
Introduction Light transmission aggregometry (LTA) is regarded as the gold standard in platelet function diagnostics. However, there is a relevant degree of interlaboratory variability in practical applications.Objective The aim of the present study was to develop a practicable laboratory comparison on LTA and to analyze differences and influencing factors in regard to standardization in five specialized hemostaseological centers.Methods The study was performed on 30 patients in total. Each center performed LTA on blood samples from six healthy volunteers (three men and three women) using the inductors collagen (Col), adenosine diphosphate (ADP), arachidonic acid (ARA), and ristocetin. The LTA was performed three times using different methods as follows: (1) International Society on Thrombosis and Haemostasis recommendations with identical reagents, (2) in-house protocols and the identical reagents; and (3) in-house protocols and in-house reagents.Results A total of 396 measurements of 30 probands were performed. Even after standardization of the protocol and using identical reagents, there were significant differences between the centers regarding the final and maximum aggregation (p = 0.002 and <0.001) and further significant differences in the maximum and final aggregation according to the wavelength of the device used to measure the LTA (PAP-8: 430 nm, APACT 4004: 740 nm [p < 0.001 each]). Using identical reagents but individual inductor concentrations and laboratory protocols also resulted in different maximum and final aggregation. The largest differences were seen with Col and ristocetin; there were significant influences from the reagents' manufacturers in the results of aggregometry for the inductor Col (p < 0.01) but not for ADP, ARA, and ristocetin.Conclusion In this study, we proved that there are significant influences from the used aggregometers, inductors concentrations, and manufacturers. These results illustrate the challenges and importance of standardization of LTA.
Keywords: inherited/acquired platelet disorders; platelet physiology; platelet immunology; platelet glycoproteins